Meeting between the Prime Minister and members of the Trades Union Congress General Council Special Industrial Committee (verbatim report) : (1926/05/01) - Trades Union Congress. General Council. Special Industrial Committee ; Baldwin, Stanley Baldwin, Earl, 1867-1947
1 May 1926